2005
DOI: 10.1029/2003jb002405
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the crust in the vicinity of the Banggong‐Nujiang suture in central Tibet from INDEPTH magnetotelluric data

Abstract: [1] Magnetotelluric data from a 150-km-long profile crossing the Banggong-Nujiang suture (BNS), central Tibet, acquired as part of the International Deep Profiling of Tibet and the Himalaya (INDEPTH) project, have been examined for crustal and upper mantle structure. Strike and dimensionality analyses demonstrate that regional-scale electrical structures are two-dimensional and oriented approximately parallel to surface geological strike. As seen elsewhere in Tibet, the double thickness crust is generally char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 121 publications
(208 reference statements)
2
26
0
1
Order By: Relevance
“…Zhang et al (1996) describe three broadband MT profiles that extended across the Qiangtang terrane and showed that a mid-crustal conductor was present in the central Tibetan Plateau. Solon et al (2005) report a more detailed study of the INDEPTH 500-line where it crossed the Bangong-Nuijiang suture (BNS) and showed an increase in the conductivity of the mid-crustal layer to the North. Mechie et al (2004) used a combined analysis of the 500-line MT data and coincident seismic reflection data to determine the depth of the a-b quartz transition.…”
Section: Regional Scale Mt Studies Of the Central And Northern Tibetamentioning
confidence: 98%
“…Zhang et al (1996) describe three broadband MT profiles that extended across the Qiangtang terrane and showed that a mid-crustal conductor was present in the central Tibetan Plateau. Solon et al (2005) report a more detailed study of the INDEPTH 500-line where it crossed the Bangong-Nuijiang suture (BNS) and showed an increase in the conductivity of the mid-crustal layer to the North. Mechie et al (2004) used a combined analysis of the 500-line MT data and coincident seismic reflection data to determine the depth of the a-b quartz transition.…”
Section: Regional Scale Mt Studies Of the Central And Northern Tibetamentioning
confidence: 98%
“…Rigorous model assessment, as discussed next, must further be applied. A more detailed description of the magnetotelluric method and its development can be found in Simpson and Bahr (2005), Jiracek et al (1995), Jones (1992), and Vozoff (1991).…”
Section: Magnetotelluric Imagingmentioning
confidence: 99%
“…BNS = Bangong-Nujiang Suture. Figure reproduced fromMechie et al (2004) using a resistivity model modified afterSolon (2000) …”
mentioning
confidence: 99%
“…Results of INDEPTH seismic and magneto-telluric soundings give indirect evidences of such process. They establish some layers of increased plasticity and partial melting of rocks in the Tibet crust at the depth 20-30 km [31,32]. The SE boundary of the Bayanhar Block coincides with the sharp step in the crust and in the whole lithosphere along the lineament of 102˚ -103˚ E [24] with intensive decreasing lithosphere thickness to the east [36].…”
Section: Interblock Zonesmentioning
confidence: 99%